ANALISIS PERILAKU ADOPSI TEKNOLOGI MOBILE WALLET MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY3 (UTAUT3) (Survei Pengguna OVO pada Generasi Milenial di Indonesia) - Ramadhan, Didit; Hurriyati, Ratih; Lisnawati, Lisnawati (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The development of technology has triggered developments in all industrial sectors, including circulation of money. There are three types of money currently circulating, namely currency, demand deposits and e-money. OVO is one of the server-based e-money publishers that can be accessed via a smartphone or commonly known as a mobile wallet. The low number of mobile wallet (m-wallet) users in Indonesia is interpreted from the number of people who use cash compared to m-wallets. Several factors influence the low use of m-wallet in Indonesia. Millennials are considered the generation closest to technology, the presence of new technology is a necessity that is owned by millennials. With this millennial generation, it is expected to be able to improve the performance or effectiveness of the presence of this m-wallet. The type of research used is descriptive verification, namely by describing and exposing the variables studied and then drawing conclusions. The research object is the variable found in the UTAUT3 model. The population in this study were OVO users in Indonesia. Sampling in this study uses non-probability sampling (random sampling) using a purposive sampling technique for 114 OVO users in the millennial generation in Indonesia. Instrument test is done by validity test and reliability test and the analysis technique used is analysis of Structural Equation Modeling based on Partial Least Square (SEM-PLS).